Activated carbon prepared from Brazil nut shells towards phenol removal from aqueous solutions (2023)
The Brazil nut shell was used as a precursor material for preparing activated carbon by chemical activation with potassium hydroxide. The obtained material (BNSAC) was characterized, and the adsorptive features of phenol were investigated. The characterization showed that the activated carbon presented several rounded cavities along the surface, with a specific surface area of 332 m2 g–1. Concerning phenol adsorption, it was favored using an adsorbent dosage of 0.75 g L–1 and pH 6. The kinetic investigation revealed that the system approached the equilibrium in around 180 min, and the Elovich model represented the kinetic curves. The Sips model well represented the equilibrium isotherms. In addition, the increase in temperature from 25 to 55 °C favored the phenol adsorption, increasing the maximum adsorption capacity value (q s) from 83 to 99 mg g–1. According to the estimated thermodynamic parameters, the adsorption was spontaneous, favorable, endothermic, and governed by physical interactions. Therefore, the Brazil nut shell proved a good precursor material for preparing efficient activated carbon for phenol removal.